Synthesis and acute toxicity of new S-derivatives (1,2,4-triazole-3(2H)-yl)methyl) thiopyrimidines - Yu. V. Karpenko; O. I. Panasenko; S. M. Kulish; A. V. Domnich (Zaporozhye State Medical University, 2023)
In the literature, there is insufficient information on the synthesis of compounds in a series of pyrimidine-2-thiol derivatives containing a five-membered nitrogen-containing heterocyclic fragment; at the same time, there are a sufficient number of examples, demonstrating the synthetic and biological potential for compounds of this kind. The relevance of the study "structure - acute toxicity" relationship in a number of newly synthesized derivatives of 1,2,4-triazole-3(2H)-thione with pyrimidine-2-thiol is due to the synthesis of potential low molecular weight interferon inducers and antitumor agents, the search for molecular descriptors of their structure, important for establishing "structure - acute toxicity" laws, as a system for evaluating the biological effects of compounds. Therefore, it is strategically and economically justified to conduct a study of the acute toxicity of synthesized compounds as a priority. The aim of the work is targeted synthesis of a number of S-derivatives (1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines and the establishment of the "structure - acute toxicity" relationship. Materials and methods. A modern set of physical-chemical research methods was used to study the compounds. The study of the acute toxicity of the synthesized compounds was performed on adult Danio rerio. During the experiments, the fish were kept on a diet for a test period of 96 hours, and their mortality was checked every 24, 48, 72 and 96 hours with the test compounds in each mini-aquarium containing at least 7 individuals of Danio rerio. Results. Results 1H NMR spectra confirm that the alkylation reaction occurs specifically on the sulfur atom. Thus, after analyzing LC50 data, we found that the least toxic among the studied compounds is 2-(((4-methyl-5-(octylthio)-4H-1,2,4-triazole-3-yl )methyl)thio)pyrimidine with an acute toxicity value of 49.66 mg/l. The most toxic compound is 2-(((4-methyl-5-(methylthio)-4H-1,2,4-triazole-3-yl)methyl)thio)pyrimidine with an LC50 value of 8.29 mg/l. The low toxicity of the compound 2-(((4-methyl-5-(octylthio)-4H-1,2,4-triazole-3-yl)methyl)thio)pyrimidine is most likely due to the presence of an octyl substituent, which sufficiently penetrates through biological membranes and does not have a strong toxic effect on organ systems. Furthermore, it does not accumulate but is metabolized in the cell. Conclusions. New hybrids of 1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines were obtained using the heterocyclization reaction of the intermediate carbothioamide. To reduce the indicators of acute toxicity and increase their biological activity, synthesized S-derivatives of this series were created. It was established that S-derivatives of 1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines belong to moderately toxic to low-toxic compounds according to the classification of D. R. Passino. 2-(((4-Methyl-5-(octylthio)-4H-1,2,4-triazole-3-yl)methyl)thio)pyrimidine has an acute toxicity value of 49.66 mg/l. The most toxic compound is 2-(((4-methyl-5-(methylthio)-4H-1,2,4-triazole-3-yl)methyl)thio)pyrimidine with an LC50 value of 8.29 mg/l.